Relationship between HIV Status, DM Status, and PMO Presence with the Success of Treatment of Productive-Age Pulmonary TB Patients - Vita Olivionita; Suhartono Suhartono; Bagoes Widjanarko; Onny Setiani; Apoina Kartini (Indonesian Journal of Global Health Research, 2024)
Data from the Semarang City Health Office shows the treatment success rate at the dr. Adhyatma, MPH Regional Hospital has decreased significantly from 2021 to 2022. Factors that influence TB treatment outcomes are important indicators of the success of the TB control program. Objective: This study aims to see the relationship between HIV status, DM status, and the presence of PMO with the success of treatment of productive-age pulmonary TB patients. Method: This study uses a retrospective cohort study design. The population in the study was 324 patients. The sampling technique used is the total sampling technique. The sample in this study were productive-age pulmonary TB patients undergoing treatment who were recorded in medical records met the inclusion and exclusion criteria totaling 79 patients. Data analysis used is the chi-square test. Results: The results of the study obtained were that there was a significant relationship between HIV status (p-value = 0.007; OR = 1.816; 95% CI = 1.467-2.247), DM status (p-value = 0.027; OR = 1.501; 95% CI = 1.086-2.075 ), and the presence of PMO (p-value = 0.028; OR = 1.486; 95% CI = 1.043-2.117 ). Conclusions: From the research that has been conducted, it can be concluded that there is a significant relationship between HIV status, DM status, and the presence of PMO with the success of treatment of productive-age pulmonary TB patients at dr. Adhyatma, MPH Regional Hospital.